What does implementing case‐centered teaching of evaluation look like in practice?. Issue 172 (24th February 2022) - Kallemeyn, Leanne M.; Roseveare, Christine; Steinberg, Marla; Tovey, Tiffany L. S.
Abstract: Rooted in the pedagogical literature, three evaluation educators, guided by a facilitator, engaged in reflective practice regarding case‐centered teaching and learning. We engaged in (D)escription, (A)nalysis, (T)heorizing, and (A)cting (DATA model) in relation to case‐centered teaching. Based on a cross‐case analysis, we identified five common actions in our teaching with cases: (1) Use case‐centered teaching in various contexts to support a variety of different learning outcomes for students from different backgrounds; (2) Choose cases intentionally; (3) Integrate student learning activities, supports, and materials; (4) Evaluate students' learning experiences with cases; and (5) Engage in collaborative reflection to facilitate learning and improvement on instructional practices with case‐centered teaching.